2017
DOI: 10.1002/anie.201611858
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Fast Supercritical Hydrothermal Synthesis of Tobermorite under Thermodynamically Metastable Conditions

Abstract: Tobermorite is a fibrillar mineral of the family of calcium silicates. In spite of not being abundant in nature, its structure and properties are reasonably well known because of its interest in the construction industry. Currently, tobermorite is synthesized by hydrothermal methods at mild temperatures. The problem is that such processes are very slow (>5 h) and temperature cannot be increased to speed them up because tobermorite is metastable over 130 °C. Furthermore the product obtained is generally foil-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 55 publications
0
37
0
Order By: Relevance
“…Nevertheless, pure crystalline tobermorite is arduous to achieve being usually associated with amorphous or poorly ordered phase. Several studies were carried out to improve the crystallinity with the study of different parameters such as reaction duration, temperature, Ca/Si ratio, pH, precursor and partial substitution of silicon by aluminum . Moreover, the effect of additives such as EDTA, sucrose, borosilicate or Ca‐formate was also the subject of many studies.…”
Section: Ultra‐fast Continuous Synthesis Of Minerals In Scwmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, pure crystalline tobermorite is arduous to achieve being usually associated with amorphous or poorly ordered phase. Several studies were carried out to improve the crystallinity with the study of different parameters such as reaction duration, temperature, Ca/Si ratio, pH, precursor and partial substitution of silicon by aluminum . Moreover, the effect of additives such as EDTA, sucrose, borosilicate or Ca‐formate was also the subject of many studies.…”
Section: Ultra‐fast Continuous Synthesis Of Minerals In Scwmentioning
confidence: 99%
“…The hydrothermal process is usually performed at 200 °C during 5 hours to 56 days . The temperature is a critical parameter since tobermorite is unstable (Ca/Si ratio not in the range of 0.8 to 1) under hydrothermal conditions and xonotlite starts to be formed at 130 °C . Notwithstanding, many researches confirmed that partial substitution of silicon by aluminum increases the stability of tobermorite …”
Section: Ultra‐fast Continuous Synthesis Of Minerals In Scwmentioning
confidence: 99%
See 3 more Smart Citations